Pathogenic homozygous variations in ACTL6B cause DECAM syndrome: Developmental delay, Epileptic encephalopathy, Cerebral Atrophy, and abnormal Myelination. Issue 8 (27th May 2019) - Yüksel, Zafer; Yazol, Merve; Gümüş, Evren
Abstract: The extensive usage of next generation sequencing, particularly for the patients affected with neurodevelopmental disorders, has increased our understanding and enabled identifying novel disorder genes. Here, we report an extended consanguineous family having at least three affected children with ACTL6B ‐related neurodevelopmental disorder and expand the known phenotypic spectrum by characterizing the clinical findings using a standardized vocabulary, Human Phenotype Ontology Terms.